Foreign exports, net interregional spillovers and Chinese regional supply chains*. (25th November 2015) - Pei, Jiansuo; Oosterhaven, Jan; Dietzenbacher, Erik
Abstract: This study develops a method to decompose total national indirect value added effects (induced by final demand) into intraregional effects and interregional spillovers. The decomposition is applied to China's 2002 and 2007 interregional input–output tables with foreign‐owned processing exports separated from normal exports. First, we find that interregional spillovers account for one quarter to one half of the total national indirect value added multipliers in 2007, with the largest spillovers occurring for the coastal regions. This finding is important when explaining regional value added generation and thus has real implications for regional policy programmes. Second, we develop a new measure, namely, 'net interregional value added spillovers' to position China's individual regions in the global production chains. This measure shows that upstream regions in the Centre, Northwest and Southwest of China are net recipients of interregional value added spillovers generated by foreign exports in coastal regions. Over time, this observation becomes more pronounced.